A Microelectrophysiologic Basis For The Fibrillation Retardant Effects Of Sulfinpyrazone And Salicylate - Iansmith, D H S; Nash, C B; Bandura, J P (Thrombosis and Haemostasis, 1981)
The antagonism of platelet function has been suggested as a mode of action for sudden death prophylaxis by sulfinpyrazone (S) and salicylates (A). To evaluate an antiarrhythmic means for such action, 5.0 to 20.0 mg/Kg A or S was administered i.v. to open-chest, intermittently cardiac paced canines in which arterial pressure and EKG were monitored. Fibrillation thresholds (FT) were measured before and after coronary arterial ligation and drug administration, by extrastimuli of increasing current strength during the vulnerable period of the T wave. Acutely both A and S increased FT 2 to 3 times that of post-infarcted values. To elucidate the mechanism for this response Purkinje fibers were isolated from the left ventricles of adult canines. These were pinned to the paraffin floor of a lucite isolation well, affixed with stimulating and surface recording electrodes, and partitioned with a plastic collar coated with vegetable fat to provide a fluid seal. Separate inflow and outflow ports allowed for individualized microenvironments for each chamber. After 60 min of tissue equilibration with well oxygenated, 36°C normal Tyrode Solution (TS), the fluid of the chamber distal to the stimulus source was altered to include 2-35 mg% A or 2-50 ugm/ml S, with or without CO2 substitution for O2 (pH 6.4) or HC1 (pH 6.4). Action potentials (AP) from each chamber were monitored during 60 min of altered TS and then 60 min of normal TS reperfusion. In a dose-dependent manner A depressed AP parameters to cause automaticity and inactivity, while S was without effect. Whereas S was able to prolong tissue survival and support electrical activity in a situation of local acidosis (if absolute hypoxia were not superimposed), A was not. Such information suggests that although both A and S are arrhythmia retardant in the postinfarction period, their modes of action may differ. Both might act as “membrane stabilizers”; however, it appears that electrogenic aberration is necessary before S manifests an effect.